Microbial community and soil fertility status as influenced by different nitrogen fixing tree species in alfisol - Meshram, Nandkishor; Dalvi, Vijay; Shigwan, Ashish; Narkhade, Satish (Indian Journal of Agroforestry, 2020)
An experimental study was conducted during 2014-15 and 2015-16 at the Research Farm of All India Coordinated Research Project on Agroforestry under Dr. Balasaheb Sawant Konkan Krishi Vidyapeeth, Dapoli, Maharashtra, to assess the impact of 22 years old nitrogen fixing trees on microbial community, soil fertility and growth attributes in alfisol (Lateritic soil). The block plantation grown with ten tree species viz., Cassia siamea, Dalbergia sissoo, Gliricidia sepium, Pterocarpus marsupium, Acacia catechu, Acacia auriculiformis, Acacia holosericea, Acacia mangium, Casuarina equisetifolia and Albizia lebbeck were selected with one absolute control (fallow). The higher improvement in growth attributes and build up in soil fertility, microbial community (viz., bacteria, actinomycetes and fungi) were noticed under A. mangium and A. auriculiformis. Higher nutrient content viz., nitrogen, phosphorus and potassium were recorded under G. sepium (available N 430.35 – 371.71 kg ha-1), P. marsupium (available P 24.22 – 15.04 kg ha-1) and A. catechu (available K 370.64 – 236.58 kg ha-1). Height (25.4 m), diameter at breast height (77.3 cm), mean annual increment (MAI), height (0.67 m) and diameter at breast height (3.73 cm) were found to be statistically higher in P. marsupium, followed by C. equisetifolia as compared to the other nitrogen fixing tree species. Among the different nitrogen fixing trees species, development of soil fertility and tree growth by A. mangium, G. sepium, P. marsupium, A. holosericea and A. catechu will be more suitable for block plantation, bund plantation, alley cropping and will be good source of nutrients if planted in agroforestry system in humid ecosystem.